2015
DOI: 10.5966/sctm.2015-0127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Fresh, Autologous Mesenchymal Stem Cells for Severe Refractory Gingivostomatitis in Cats

Abstract: The use of fresh, autologous, adipose-derived mesenchymal stem cells (ASCs) was studied for treatment of feline chronic gingivostomatitis. Cats received autologous ASCs, and immunomodulatory effects were assessed. The five cats that responded to treatment also exhibited systemic immunomodulation. Response to ASC therapy was seen only in cats with <15% CD8lo cells, suggesting relative absence of CD8lo cells may be a biomarker of treatment response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
190
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(209 citation statements)
references
References 66 publications
14
190
0
5
Order By: Relevance
“…Our previous work demonstrated that cats with FCGS have increased percentages of blood CD81 T cells with a resultant decreased CD4/ CD8 T cell ratio [1]. The cats in this study generally recapitulated this phenotype (Fig.…”
Section: Allogenic Asc Administration Did Not Predictably Alter Bloodsupporting
confidence: 78%
See 2 more Smart Citations
“…Our previous work demonstrated that cats with FCGS have increased percentages of blood CD81 T cells with a resultant decreased CD4/ CD8 T cell ratio [1]. The cats in this study generally recapitulated this phenotype (Fig.…”
Section: Allogenic Asc Administration Did Not Predictably Alter Bloodsupporting
confidence: 78%
“…E) as measured by BrdU incorporation. There was no difference in lymphocyte suppressive ability between the three SPF allogenic ASC lines used in this study and the autologous ASC lines used in the previous study .…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Cats are a particularly important translational model for a number of diseases that are similar in cats and humans, including FIV (HIV) [61], T cell-mediated oral mucosa inflammation [24], chronic renal failure [29], asthma [25], chronic enteropathy [26], and osteoarthritis. The goal of this work was to profile feline ASCs and directly compare their phenotypic, cellular, and immunomodulatory profiles with human ASCs to deepen our understanding of MSC-based therapies as we move towards mechanism-of-action studies in animals and people.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of Th17 cells and the cytokine IL-17 in the pathogenesis of some infectious diseases in some of the non-rodent animals has been described (116, 121). However, most of these studies are observational, and cells were isolated from peripheral blood samples only.…”
Section: Comparison Of Treg and Th17 Response In Humans Rodents Andmentioning
confidence: 99%